2018
DOI: 10.1002/bio.3531
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive resonance Rayleigh light scattering method for alpinetin using gold nanorods probes

Abstract: A sensitive resonance Rayleigh light scattering (RLS) assay for alpinetin was developed based on alpinetin-modified gold nanorods (AuNRs). Alpinetin could interact with AuNRs and formed a new assembly by electrostatic attraction. In pH 7.4 Tris-HCl buffer solution, the assembly of alpinetin-AuNRs showed a sensitive RLS signal. Under optimum conditions, the magnitude of enhanced RLS intensity (ΔI ) was proportional to the concentration of alpinetin over the range 0.027-3.24 μg ml , with a detection limit of 1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently, it has been reported that alpinetin may be deemed as a good candidate for some possible treatment of liver injury and brain diseases [12,13]. Because of its multiple therapeutic activities, alpinetin is considered as a potential candidate drug for further clinical studies, and has recently attracted more and more attention from medical and pharmaceutical fields [14,15,16]. Therefore, a better understanding of the efficacy of alpinetin needs to elucidate its biological fate in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that alpinetin may be deemed as a good candidate for some possible treatment of liver injury and brain diseases [12,13]. Because of its multiple therapeutic activities, alpinetin is considered as a potential candidate drug for further clinical studies, and has recently attracted more and more attention from medical and pharmaceutical fields [14,15,16]. Therefore, a better understanding of the efficacy of alpinetin needs to elucidate its biological fate in the body.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, alpinetin was also widely found in many other medicinal herbs and has been abstracted from Alpinia hainanensis K. Schum. [Zingiberaceae] (Rao and Lin, 1998;Liang et al, 2007;Liu et al, 2007;Wang et al, 2007;Liu and Wu, 2009;Li et al, 2010;Zou and Lu, 2011;Zhao et al, 2013;Bi et al, 2018), Alpinia mutica Roxb. [Zingiberaceae] (Malami et al, 2016;Malami et al, 2017a), Alpinia pinnanensis T. L. Wu & S. J.…”
Section: Introductionmentioning
confidence: 99%
“…The natural sources of alpinetin were listed in Table 1. The accurate methods for the separation and determination of alpinetin were developed by highperformance liquid chromatography (HPLC), combination of flow injection (FI)-micellar electrokinetic chromatography (MEKC), reverse micelle electrokinetic capillary chromatography (RMEKC), sensitive resonance Rayleigh light scattering (RLS) assay, and liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Liu et al, 2007;Wang et al, 2007;Singh et al, 2015;Bi et al, 2018;Lorençoni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%